OPTIMIZATION OF SCHIZOCHYTRIUM LIMACINUM BIOMASS AND LIPID PRODUCTION USING PALM SAP SUGAR MEDIUM WITH VARIATION OF SALINITY CONCENTRATION - Fadhilatunnisa, Najwa
Thraustochytrid, known as heterotrophic marine protists, in particular Schizochytrium limacinum has become an organism that has attracted attention in the development of biotechnology because of its ability to accumulate lipids naturally, especially in the form of PUFA. Under optimized conditions, the resulting lipid content S. limacinum can reach 30-50% of its dry weight. To produce these lipids, attention is needed to several factors that can influence the level of biomass and lipid production in S. limacinum, one of the carbon sources in the growth medium used. In this research, palm sap sugar which consists of various sugar components is used as an alternative carbon source that supports growth S. limacinum and is believed to be able to increase the efficiency value from an economic perspective to compete with other lipid-producing organisms. Apart from carbon sources, other environmental factors such as medium salinity are known to influence biomass and lipid production by S. limacinum So this research aims to determine the optimum medium salinity concentration for biomass and lipid productivity in cultivation S. limacinum in palm sap sugar medium. This research was carried out by cultivating S. limacinum in palm sap sugar medium using three variations of medium salinity concentration, namely 1%, 3%, and 5% (w/v) with incubation conditions at room temperature, initial pH 5-6, agitation 150 rpm, and initial inoculum concentration 10% for 120 hours. Biomass harvesting every 12 hours is carried out to create a growth curve S. limacinum. Lipids then extracted from dry biomass based on the Weibull-Stoldt method using n-hexane solvent. The highest biomass productivity of S. limacinum (0.187 ± 0.024 g/L.day) was obtained at a salinity variation of 3% (w/v). The highest yields of lipid fraction (37.30% (w/w)), total lipid (0.497 g/L) and lipid productivity (0.105 g/L.day) were obtained at a 3% (w/v) salinity variation. Through statistical analysis one-way ANOVA, the variation in salinity used did not make a significant difference to biomass productivity (p-value > 0.05). The conclusion of this research is that a 3% (w/v) variation in salinity provides the highest biomass and lipid productivity in cultivation S. limacinum in palm sap sugar.